Review Model Pengelolaan Limbah Domestik Warga DKI Jakarta - Saman, Samsudin; Astra, I Made; Hasanah, Uswatun (Universitas Trunojoyo Madura, 2023)
Surface and ground water pollution that occurs in DKI Jakarta shows an increasing trend. Efforts to develop centralized household domestic wastewater treatment which had been initiated by the DKI Jakarta Provincial Government since 1972 have been progressing very slowly. A lot of research has been carried out and can be used as a reference, but not much has discussed the sustainability of holistic domestic wastewater management. The concept of sustainable development is basically how to place ecological, economic and social aspects as an inseparable unit so that it can meet the needs of the current generation without reducing the ability of future generations to meet their needs. The waste water management system implemented by the DKI Jakarta Provincial Government is still partial and not holistic. The research results show that waste water management in DKI Jakarta is at a less sustainable status. For this reason, determining priority strategies to achieve the objectives of the waste management development program and formulating strategies for developing domestic waste management, including reducing the level of water pollution, financing development, selecting technology, handling social problems, providing land, developing institutions and increasing community participation, needs to be carried out. for the sustainability of domestic wastewater management in DKI Jakarta.